Awareness of waqf among the people of Afghanistan - Mangal, Rahmatullah (IIUM Institute of Banking and Finance, International Islamic University Malaysia, 2019)
Waqf attracted the attention of scholars because of its unique and various aspects, especially cash waqf which has been used for poverty alleviation. Waqf was quite popular in Afghanistan four hundred years ago at the era of Ghaznavid and Timurid, nonetheless currently it is minimal because of last forty years of war and limited to mosque and religious buildings. The main objective of this study to explore the awareness level of the people in Afghanistan about waqf. In This research we conducted the quantitative method and adopted and used a questionnaire and collected the data from 270 respondents. Data has been analyzed by using (SPSS). In this study the finding demonstrate that the primary knowledge about waqf is in average however their knowledge regarding some specific characteristics of waqf is quite low. In addition the level of awareness is also low same like knowledge, nonetheless there awareness of current practice of waqf is quite low. The study has also found that there is a significant relationship between knowledge, awareness, religiosity and intention where all independent variable impact the intention (DV) of people to contribute in waqf. In this research it is advisable to the regulators and Muslim scholars to increase the knowledge level of public regarding waqf and its role in improving the welfare of the less privileged segment of the community. This study will increase awareness and knowledge level of the policy makers, and will contribute them how to manage and use the waqf for public welfare and poverty alleviation in Afghanistan.